Evaluation of the diabetes care cascade and compliance with WHO global coverage targets in Iran based on STEPS survey 2021 - Sina Azadnajafabad; Naser Ahmadi; Negar Rezaei; Mohammad-Mahdi Rashidi; Sahar Saeedi Moghaddam; Esmaeil Mohammadi; Mohsen Abbasi-Kangevari; Mohammadreza Naderian; Erfan Ghasemi; Yosef Farzi; Ameneh Kazemi; Arezou Dilmaghani-Marand; et al. (Scientific Reports, 2023)
This study aimed to investigate the diabetes mellitus (DM) and prediabetes epidemiology, care cascade, and compliance with global coverage targets. We recruited the results of the nationally representative Iran STEPS Survey 2021. Diabetes and prediabetes were two main outcomes. Diabetes awareness, treatment coverage, and glycemic control were calculated for all population with diabetes to investigate the care cascade. Four global coverage targets for diabetes developed by the World Health Organization were adopted to assess the DM diagnosis and control status. Among 18,119 participants, the national prevalence of DM and prediabetes were 14.2% (95% confidence interval 13.4–14.9) and 24.8% (23.9–25.7), respectively. The prevalence of DM treatment coverage was 65.0% (62.4–67.7), while the prevalence of good (HbA1C0.167em<0.167em7%) glycemic control was 28.0% (25.0–31.0) among all individuals with diabetes. DM diagnosis and statin use statics were close to global targets (73.3% vs 80%, and 50.1% vs 60%); however, good glycemic control and strict blood pressure control statistics, were much way behind the goals (36.7% vs 80%, and 28.5% vs 80%). A major proportion of the Iranian population are affected by DM and prediabetes, and glycemic control is poorly achieved, indicating a sub-optimal care for diabetes and comorbidities like hypertension.
Keywords: 330